Ceramic and specialty electrolytes for energy storage devices - Raghavan, Prasanth; Jabeen Fatima M. J. (Boca Raton : CRC Press, 2021)
"This book will be of high value to researchers and engineers working on the development of next-generation energy storage devices, including materials and chemical engineers, as well as those involved in related disciplines"--
Solid state electrolytes for lithium ion batteries : performance requirements and ion transportation mechanism in solid polymer electrolytes / Jabeen Fatima M. J, Abhijith P. P, Jishnu N. S, Akhila Das, Neethu T.M. Balakrishnan, Jou-Hyeon Ahn, Raghavan Prasanth.
OCLC-licensed vendor bibliographic record.
Keywords: Storage batteries -- Materials; Solid state batteries -- Materials; Electronic ceramics; Electrolytes; TECHNOLOGY / Material Science; SCIENCE / Chemistry / Industrial & Technical